News Digest - Refuge Editor (Refuge: Canada’s Journal on Refugees, 1985)
Olof Rydbeck, Commissioner- General of the United Nations Relief and Works Agency for Palestine Refugees (UNRWA) since 1979, retired on 31 October after a long and distinguished career, and has been replaced by Giorgio Giacomelli of Italy. Giacomelli has been Director-General of the Department of Co-operation and Development in the Italian Foreign Ministry since 1981.